Commodity Bonds and Consumption Risks - O'Hara, Maureen (Journal of Finance, 1984)
This paper analyzes the economic role of commodity bonds by examining the nature of the demand for these securities. I show that while commodity bonds protect against relative price changes, they do so by introducing variability into the future real income stream. This variability limits the desirability of using commodity bonds to provide “price insurance” for future consumption. However, this variability may allow commodity bonds to hedge risks to consumption caused by stochastic changes in income. The analysis also suggests that it is this “income insurance” rather than “price insurance” that is important in hedging risks to future consumption.